Polyethylene glycol coated carbon nanotube fiber composite material and preparation method thereof
By functionalizing the carbon nanotubes and coupling with polyethylene glycol, a polyethylene glycol-coated carbon nanotube fiber composite material is formed, which solves the shortcomings of existing flexible electronic materials in terms of conductivity, mechanical strength, flexibility and stability, and achieves a combination of high conductivity and mechanical properties, which is suitable for the preparation of flexible electronic devices.
Patent Information
- Application Number
- CN202411232480.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
Existing flexible electronic materials have shortcomings in electrical conductivity, mechanical strength, flexibility and stability, and it is difficult to meet the performance requirements of flexible wearable optoelectronic devices.
By functionalizing the carbon nanotubes and coupling with polyethylene glycol, a polyethylene glycol-coated carbon nanotube fiber composite material is formed, which reduces the contact resistance between the carbon nanotubes and enhances the conductivity and mechanical properties of the material.
It improves the dispersion of carbon nanotubes in solvents, enhances the conductivity and mechanical properties of the material, maintains flexibility and chemical stability, and is suitable for the preparation of flexible electronic devices.
Smart Images

Figure CN119613787A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano and composite materials, and in particular to a polyethylene glycol-coated carbon nanotube fiber composite material and a preparation method thereof. Background Art
[0002] In the flexible electronics industry, the demand for functional materials is increasing day by day. As the core component of future smart electronic products, flexible wearable optoelectronic devices have received widespread attention. These devices need to be lightweight and bendable, and are widely used in smart clothing, health monitoring, human-computer interaction, and energy collection and storage.
[0003] The performance of optoelectronic devices depends largely on the conductivity, mechanical strength, flexibility and stability of their internal materials. The materials commonly used to prepare flexible wearable optoelectronic synaptic devices mainly include the following: conductive polymer materials, two-dimensional materials, nanowires, flexible substrate materials, etc.
[0004] Conductive polymer materials, such as polypyrrole (PPy), polyaniline (PANI), poly(3,4-ethylenedioxythiophene), PEDOT, etc., usually have poor chemical and thermal stability and are prone to performance degradation under the influence of external environmental factors (such as temperature and humidity). In addition, these materials also have poor mechanical strength and environmental stability (such as oxidation resistance and moisture resistance). Weak mechanical strength and flexibility, poor electrical conductivity, poor thermal stability, and low interface compatibility are all problems that need to be solved.
[0005] Two-dimensional materials, such as graphene and MoS2, have excellent electronic properties, but their adhesion on flexible substrates may be weak and their processing costs are high.
[0006] Flexible substrate materials, such as polyethylene terephthalate (PET), polyimide (PI) and polydimethylsiloxane (PDMS), have insufficient mechanical properties and are prone to cracks and deformation, affecting the stability and reliability of the device. In addition, its surface roughness is high, which can easily affect the optoelectronic performance and transmission efficiency of the device.
[0007] Based on the defects of the above materials, it is necessary to design a material with good mechanical strength and flexibility, high chemical stability and excellent electrical conductivity to facilitate subsequent processing and use.
[0008] Carbon Nanotubes (CNTs) are a unique nanoscale material, formed by carbon atoms arranged in a specific way to form a tubular structure. The diameter of these tubular structures is at the nanometer level, and the length can reach several microns or even longer, so carbon nanotubes have a high aspect ratio. Carbon nanotubes have very high electrical conductivity, which is crucial for the transmission of electrons or holes, and helps to improve the electronic transmission efficiency and response speed of the device.
[0009] In addition, it has good tensile strength and elasticity, which means it can withstand large bends without deforming or breaking, making it suitable for bendable and stretchable optoelectronic applications.
[0010] However, carbon nanotubes tend to form clusters in solution and are not easy to disperse evenly. Good dispersion is critical to ensuring charge transfer within flexible devices. In addition, the contact resistance between pure carbon nanotubes is high. If not treated, the overall resistance of the device will increase, resulting in a decrease in electrical performance.
[0011] To overcome these defects, special polymer dispersants must be used to help improve the dispersion of carbon nanotubes in solvents and form stable composite materials with carbon nanotubes during the preparation process. This can not only improve the dispersion of carbon nanotubes, but also improve the mechanical and electrical properties of the entire film through the polymer matrix. Summary of the invention
[0012] The purpose of the present invention is to overcome the problems existing in the prior art and provide a polyethylene glycol-coated carbon nanotube fiber composite material and a preparation method thereof. The method reduces the contact resistance between carbon nanotubes by polymerizing polyethylene glycol between carbon nanotubes, enhances the conductivity of the material, and maintains a certain flexibility and mechanical strength.
[0013] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions: A polyethylene glycol-coated carbon nanotube fiber composite material, It comprises a substrate and a mixed solution spin-coated on the surface of the substrate: wherein, The solution is a composite solution of carbon nanotubes and polyethylene glycol.
[0014] Furthermore, the carbon nanotubes are single-walled carbon nanotubes SWCNTs, the length of which is controlled within the range of 0.5-2 μm, and the polyethylene glycol is dissolved in the ethanol solution.
[0015] Furthermore, the substrate is made of polyethylene terephthalate film PET.
[0016] A method for preparing a polyethylene glycol-coated carbon nanotube fiber composite material, the method comprising the following steps: Step S1: functionalization of carbon nanotubes, Addition of hydroxyl group -COOH; Treating single-walled carbon nanotubes SWCNTs with a mixed acid, mixing them with the mixed acid, and performing the treatment for a period of time under heating and stirring conditions, for introducing carboxyl groups on the surface of the carbon nanotubes to make them more easily dispersed in polar solvents; After the reaction is completed, the mixture is washed with deionized water to remove residual acid and by-products, and finally dried to obtain the modified carbon nanotubes with functional groups on the surface; Step S2: coupling carbon nanotubes with polyethylene glycol, Carbodiimide EDC and N-hydroxysuccinimide NHS were used to activate the carboxyl groups; The single-walled carbon nanotubes (SWCNTs) containing carboxyl groups are mixed with carbodiimide (EDC) and N-hydroxysuccinimide (NHS) in a buffer solution and reacted at room temperature for a period of time to ensure that the carboxyl groups are fully activated. The activated single-walled carbon nanotubes (SWCNTs) are added into a polyethylene glycol (PEG) solution containing terminal hydroxyl groups; After the reaction is completed, unreacted carbodiimide EDC, N-hydroxysuccinimide NHS and excess polyethylene glycol PEG are removed by centrifugation; After cleaning, dry the product for subsequent use; Step S3: solution mixing, The carbon nanotubes that have undergone coupling reaction are mixed with polyethylene glycol PEG in a solution to promote the combination of the two; Weigh the amount of polyethylene glycol PEG, add it into N,N-dimethylformamide DMF, and stir until it is completely dissolved; The functionalized carbon nanotubes are gradually added into a solution containing polyethylene glycol PEG; Using ultrasonic treatment to help disperse the carbon nanotubes in the solution; The mixed solution is stirred at room temperature for a certain period of time to ensure that the carbon nanotubes and polyethylene glycol PEG are fully reacted and form a uniform mixture; Purify the solution by filtering and allowing to stand; Step S4: using centrifugation to further purify and separate to remove uncoated carbon nanotubes or impurities; Step S5: After obtaining the mixed solution of carbon nanotubes and polyethylene glycol (PEG), the solution is spin-coated on a polyethylene terephthalate (PET) film substrate using a spin coating method to prepare a thin film that is both flexible and conductive.
[0017] Furthermore, in step S1, the mixed acid is a mixture of sulfuric acid and nitric acid.
[0018] Furthermore, the volume ratio of sulfuric acid to nitric acid is 3:1.
[0019] Furthermore, in step S2, the buffer solution is preferably a phosphate buffer solution (PBS) with a pH value of 4.5 to 7.
[0020] The beneficial effects of the present invention are: 1. The polyethylene glycol of the present invention can improve the dispersibility of carbon nanotubes in various solvents, which is of great significance for the preparation of uniform nanomaterials.
[0021] 2. Polyethylene glycol has good biocompatibility, making this material suitable for applications with long-term contact with the skin, such as wearable devices.
[0022] 3. Carbon nanotubes have excellent mechanical strength and flexibility. After being coated with polyethylene glycol, this property can be further optimized, making them suitable for making flexible electronic devices.
[0023] 4. Carbon nanotubes themselves have high conductivity. Polyethylene glycol coating can protect the electrical properties of carbon nanotubes while improving their stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the process flow for preparing flexible optoelectronic carbon nanotube devices; Figure 2 Schematic diagram of spin coating of a mixed solution of carbon nanotubes and polyethylene glycol on a polyethylene terephthalate film substrate; Figure 3 This is a schematic diagram of the epitaxial structure of a photoelectric sensor prepared based on a polyethylene glycol-coated carbon nanotube material in Application Example 1 of the present invention; Figure 4 This is a schematic diagram of the epitaxial structure of a photoelectric sensor prepared based on a polyethylene glycol-coated carbon nanotube material in Application Example 2 of the present invention.
[0025] Figure 5 This is a schematic diagram of the epitaxial structure of a PEG-CNT enhanced GaN nanowire photoelectric sensor in Application Example 3 of the present invention. DETAILED DESCRIPTION
[0026] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments.
[0027] A polyethylene glycol-coated carbon nanotube fiber composite material, It comprises a substrate and a mixed solution spin-coated on the surface of the substrate: wherein, The solution is a composite solution of carbon nanotubes and polyethylene glycol.
[0028] The carbon nanotubes are single-walled carbon nanotubes SWCNTs, the length of which is controlled within the range of 0.5-2 μm, and the polyethylene glycol is dissolved in the ethanol solution.
[0029] The substrate is made of polyethylene terephthalate film PET.
[0030] A method for preparing a polyethylene glycol-coated carbon nanotube fiber composite material, the method comprising the following steps: Step S1: functionalization of carbon nanotubes. Since carbon nanotubes have poor dispersibility in solvents, it is necessary to functionalize the carbon nanotubes so that their surfaces have functional groups. Addition of hydroxyl group -COOH; Treating single-walled carbon nanotubes SWCNTs with a mixed acid, mixing them with the mixed acid, and performing the treatment under heating and stirring for a period of time, generally several hours, to introduce carboxyl groups on the surface of the carbon nanotubes, making them more easily dispersed in polar solvents; After the reaction is completed, the mixture is washed with deionized water to remove residual acid and by-products, and finally dried to obtain the modified carbon nanotubes with functional groups on the surface; Step S2: coupling carbon nanotubes with polyethylene glycol, Carboxyl groups were activated using carbodiimide EDC (EDC, 1-ethyl-3-(3-dimethylaminopropyl)) and N-hydroxysuccinimide NHS; The single-walled carbon nanotubes SWCNTs containing carboxyl groups are mixed with carbodiimide EDC and N-hydroxysuccinimide NHS in a buffer solution and reacted at room temperature for a period of time, preferably 1 to 2 hours, to ensure that the carboxyl groups are fully activated; The activated single-walled carbon nanotubes (SWCNTs) are added into a polyethylene glycol (PEG) solution containing terminal hydroxyl groups; After the reaction is completed, unreacted carbodiimide EDC, N-hydroxysuccinimide NHS and excess polyethylene glycol PEG are removed by centrifugation; After cleaning, dry the product for subsequent use; Step S3: solution mixing, The carbon nanotubes that have undergone coupling reaction are mixed with polyethylene glycol PEG in a solution to promote the combination of the two; Weigh the amount of polyethylene glycol PEG, add it into N,N-dimethylformamide DMF, and stir until it is completely dissolved; The functionalized carbon nanotubes are gradually added into a solution containing polyethylene glycol PEG; Using ultrasonic treatment to help disperse the carbon nanotubes in the solution; The mixed solution is stirred at room temperature for a certain period of time to ensure that the carbon nanotubes and polyethylene glycol PEG are fully reacted and form a uniform mixture. The viscosity and other physical properties of the final solution are controlled by adjusting the concentration of polyethylene glycol or further diluting the solution as needed; Purify the solution by filtering and allowing to stand; Step S4: using centrifugation to further purify and separate to remove uncoated carbon nanotubes or impurities; Step S5: After obtaining the mixed solution of carbon nanotubes and polyethylene glycol PEG, the solution is spin-coated on a polyethylene terephthalate film PET substrate using a spin coating method to form a thin film that is both flexible and conductive. The schematic diagram of the spin coating process is shown in FIG. Figure 1 shown.
[0031] In step S1, the mixed acid is a mixture of sulfuric acid and nitric acid.
[0032] The volume ratio of sulfuric acid to nitric acid is 3:1.
[0033] In the step S2, the buffer solution is preferably a phosphate buffer solution (PBS) with a pH value of 4.5 to 7.
[0034] Application Example 1 1. Hot-press or naturally dry the polyethylene glycol-coated carbon nanotube film to form a conductive path.
[0035] 2. Monitor strain by changing resistance when stretched or compressed. The conductivity of carbon nanotubes changes when the material is deformed, thus enabling strain monitoring.
[0036] 3. Use the resistance change of the sensor to monitor physiological changes such as heart rate and breathing. For example, the sensor can be placed on the chest to measure the breathing rate by monitoring the expansion and contraction of the chest.
[0037] 4. Performance test: Carbon nanotubes have excellent conductivity and polyethylene glycol has good flexibility. They can be used to prepare sensors for real-time monitoring of physiological information such as human movement, heart rate, and respiration in flexible wearable designs.
[0038] Application Example 2 1. First, make a PDMS substrate, mix the PDMS precursor and hardener in a suitable ratio; degas the mixed PDMS solution in a vacuum to remove bubbles in the solution; pour the degassed PDMS solution into the pre-prepared mold; and place it in an oven for curing (curing at 60-80°C for 4 hours). After curing, remove the PDMS film from the mold.
[0039] 2. Prepare polyethylene glycol-coated carbon nanotube fiber material.
[0040] 3. Cut the Cu sheet according to the design as the electrode material; paste or transfer the Cu sheet to the PDMS film by physical or chemical methods; if necessary, pattern the electrode by etching or other methods.
[0041] 4. Precisely place the polyethylene glycol-coated carbon nanotube fiber film between the PDMS substrate and the Cu electrode; connect the electrode to the external circuit by welding; it should be noted that this step requires ensuring that all layers are in close contact to facilitate accurate signal transmission.
[0042] 5. Finally, test the pressure response ability of the smart skin, including sensitivity, stability and reliability; and make corresponding adjustments to the structure and materials based on the test results to optimize performance.
[0043] Application Example 3 1. Accurately weigh the PDMS precursor and curing agent and mix them in the ratio recommended by the manufacturer (10:1). Use a magnetic stirrer or stir manually to ensure that the precursor and curing agent are fully mixed. Transfer the mixed PDMS solution to a vacuum degasser to remove bubbles generated during the mixing process. The degassing time is 20-30 minutes. Pour the degassed PDMS solution into the pre-set mold, and adjust the thickness according to the sensor design requirements. Place it in an oven at a preset temperature (60-80°C) and cure for 4 hours to ensure that the PDMS is fully cured. Carefully remove the PDMS film from the mold as a flexible substrate for the sensor.
[0044] 2. Deposit a layer of conductive silver nanowires on the substrate as electrodes to collect and transmit photocurrent.
[0045] 3. Deposit GaN nanowires on the conductive layer. GaN nanowires serve as a photoelectric conversion layer, responsible for generating electron-hole pairs under ultraviolet light. The deposition of GaN is done by MBE (molecular beam epitaxy) technology.
[0046] 4. Drop or spray the PEG-coated CNTs dispersion onto the GaN nanowire layer. This improves the mechanical stability of the sensor and acts as an electron transport layer to help collect and transport charge carriers generated by the GaN nanowires. The PEG coating increases the dispersibility and biocompatibility of CNTs and reduces the possibility of agglomeration.
[0047] 5. Finally, a layer of silver nanowires is deposited on the CNT layer as the second electrode to form a complete circuit.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polyethylene glycol-coated carbon nanotube fiber composite material, characterized in that: It comprises a substrate and a mixed solution spin-coated on the surface of the substrate: wherein, The solution is a composite solution of carbon nanotubes and polyethylene glycol.
2. The polyethylene glycol-coated carbon nanotube fiber composite material according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes SWCNTs, the length of which is controlled within the range of 0.5-2 μm, and the polyethylene glycol is dissolved in the ethanol solution.
3. The polyethylene glycol-coated carbon nanotube fiber composite material according to claim 1, characterized in that: The substrate is made of polyethylene terephthalate film PET.
4. A method for preparing a polyethylene glycol-coated carbon nanotube fiber composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step S1: functionalization of carbon nanotubes, Addition of hydroxyl group -COOH; Treating single-walled carbon nanotubes SWCNTs with a mixed acid, mixing them with the mixed acid, and performing the treatment for a period of time under heating and stirring conditions, for introducing carboxyl groups on the surface of the carbon nanotubes to make them more easily dispersed in polar solvents; After the reaction is completed, the mixture is washed with deionized water to remove residual acid and by-products, and finally dried to obtain the modified carbon nanotubes with functional groups on the surface; Step S2: coupling carbon nanotubes with polyethylene glycol, Carbodiimide EDC and N-hydroxysuccinimide NHS were used to activate the carboxyl groups; The single-walled carbon nanotubes (SWCNTs) containing carboxyl groups are mixed with carbodiimide (EDC) and N-hydroxysuccinimide (NHS) in a buffer solution and reacted at room temperature for a period of time to ensure that the carboxyl groups are fully activated. The activated single-walled carbon nanotubes (SWCNTs) are added into a polyethylene glycol (PEG) solution containing terminal hydroxyl groups; After the reaction is completed, unreacted carbodiimide EDC, N-hydroxysuccinimide NHS and excess polyethylene glycol PEG are removed by centrifugation; After cleaning, dry the product for subsequent use; Step S3: solution mixing, The carbon nanotubes that have undergone coupling reaction are mixed with polyethylene glycol PEG in a solution to promote the combination of the two; Weigh the amount of polyethylene glycol PEG, add it into N,N-dimethylformamide DMF, and stir until it is completely dissolved; The functionalized carbon nanotubes are gradually added into a solution containing polyethylene glycol PEG; Using ultrasonic treatment to help disperse the carbon nanotubes in the solution; The mixed solution is stirred at room temperature for a certain period of time to ensure that the carbon nanotubes and polyethylene glycol PEG are fully reacted and form a uniform mixture; Purify the solution by filtering and allowing to stand; Step S4: using centrifugation to further purify and separate to remove uncoated carbon nanotubes or impurities; Step S5: After obtaining the mixed solution of carbon nanotubes and polyethylene glycol (PEG), the solution is spin-coated on a polyethylene terephthalate (PET) film substrate using a spin coating method to prepare a thin film that is both flexible and conductive.
5. The method for preparing the polyethylene glycol-coated carbon nanotube fiber composite material according to claim 4, characterized in that: In step S1, the mixed acid is a mixture of sulfuric acid and nitric acid.
6. The polyethylene glycol-coated carbon nanotube fiber composite material and the preparation method thereof according to claim 5, characterized in that: The volume ratio of sulfuric acid to nitric acid is 3:
1.
7. The polyethylene glycol-coated carbon nanotube fiber composite material and the preparation method thereof according to claim 4, characterized in that: In the step S2, the buffer solution is preferably a phosphate buffer solution (PBS) with a pH value of 4.5 to 7.